Clinical Relevance of Molecular Diagnosis in Patients with Congenital Hypothyroidism - Nicola, Juan Pablo (2017)
Congenital hypothyroidism, defined as the functional deficiency of thyroid hormones present at birth, occurs in approximately 1: 2,000 to 4,000 newborns. Thyroid hormones play an essential role in the maturation of the central nervous system. Congenital hypothyroidism results in severe neurodevelopmental impairment if untreated and, therefore constitutes the most common preventable endocrine cause of irreversible mental retardation. As clinical diagnosis of hypothyroidism in the newborn period is almost always overlooked, newborn screening programs seeking to identify elevated thyrotropin levels at birth are available to detect primary congenital hypothyroidism mainly. Significantly, early onset on levothyroxine replacement therapy virtually abolishes severe intellectual development. Congenital hypothyroidism is caused by genetic defects occurring at three different levels, including the hypothalamic-pituitary axis, the thyroid gland, and the peripheral tissues. Up to date, 30 monogenic forms of congenital hypothyroidism have been reported in individuals with thyroid dysgenesis, thyroid dyshormonogenesis, central and peripheral hypothyroidism, highlighting the genetic heterogeneity of the disease. This mini-review summarizes the latest advances in the genetic basis of monogenic forms of congenital hypothyroidism and novel strategies to uncover the molecular etiology of the disease. Moreover, the article provides the current knowledge and future perspectives on the clinical relevance of the molecular diagnosis in patients with congenital hypothyroidism.